2012
DOI: 10.1080/01634372.2012.708389
|View full text |Cite
|
Sign up to set email alerts
|

Managing in the Trenches of Consumer Care: The Challenges of Understanding and Initiating the Advance Care Planning Process

Abstract: To better understand how community-based long-term care providers define advance care planning and their role in the process, we conducted 8 focus groups with 62 care managers (social workers and registered nurses) providing care for Ohio's Medicaid waiver program. Care managers shared that most consumers had little understanding of advance care planning. The care managers defined it broadly, including legal documentation, social aspects, medical considerations, ongoing communication, and consumer education. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
37
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 15 publications
1
37
0
Order By: Relevance
“…Meanwhile, some studies claim AD should be part of nurses’ practice, but it should not be a priority when caring for patients [28]. In other studies, nurses viewed the AD application as a task for a multidisciplinary team, but the sharing of responsibility was not clear so far [2931]. Accordingly, more than half of the respondents in our study indicated the management of AD as the sharing of moral responsibility between health professional and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some studies claim AD should be part of nurses’ practice, but it should not be a priority when caring for patients [28]. In other studies, nurses viewed the AD application as a task for a multidisciplinary team, but the sharing of responsibility was not clear so far [2931]. Accordingly, more than half of the respondents in our study indicated the management of AD as the sharing of moral responsibility between health professional and the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Training and education in ACP is important. With increased training and policies tailored for community needs, US health professionals reported higher levels of confidence and comfort (Baughman et al 2012) and, for rural Victorian physicians, selfconfidence in ACP was enhanced after training (Detering et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This study is an expansion of our previous work examining ACP performed in the home and initiated by care managers (CMs) with expertise as registered nurses or social workers. In the past, we have used, separately, quantitative data to determine CM and consumer factors that influence the decision to initiate ACP conversations (Baughman et al., ), and qualitative data to explore how CMs define ACP and their role in the process (Baughman et al., ) and the narrative stories they told about ACP (Baughman, Aultman, Ludwick, & O'Neil, ). We did not analyse how merging and comparing the qualitative and quantitative data might better inform the diversity of attitudes, beliefs and perspectives of CM participants as they engage in ACP discussions.…”
Section: Introductionmentioning
confidence: 99%